PENGARUH METODE INKUIRI TERBIMBING TERHADAP KEMAMPUAN PENALARAN DAN SELF CONFIDENCE SISWA SMP - Neti Nuryanti; Tina Rosyana; Euis Eti Rohaeti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to examine the achievement of mathematical reasoning ability and self confidence of MTs students using guided inquiry method compared with using ordinary learning. The method used in this study is a quasi-experimental method, with a pretest and postes experimental-control group design. The population in this study is all MTs students in West Bandung regency, while the sample of the research is as much as two classes are selected to be experimental class and control class. The experimental class gained learning by guided inquiry method and the control class gained regular learning. The instrument used is a matter of reasoning ability test and non test self confidence matter. Data of research result are tested and analyzed quantitatively by using statistical test (t test). The conclusions obtained are as follows: 1) students' mathematical reasoning ability that obtains learning with guided inquiry method is better than students who gain ordinary learning; 2) the ability of self confidence students who gain learning with guided inquiry method is better than students who get regular learning.